PENGARUH PELATIHAN DAN STRES KERJA TERHADAP KINERJA KARYAWAN PT. CIPTA MANDIRI AGUNG JAYA BANDAR UDARA SOEKARNO HATTA - Firli Yudo Syakirah; Irma Sari Octaviani (Al Hasanah Barokah Foundation, 2025)
The purpose of this research is to find out the influence of training and work stress on employee performance at PT. Cipta Mandiri Agung Jaya Soekarno Hatta Airport both partially and simultaneously. The method used is the quantitative method. The sampling technique uses saturated sampling and 97 respondents were obtained in this study. Data analysis uses validity test, reliability test, classical assumption test, regression analysis test, correlation coefficient analysis, determination coefficient analysis, and hypothesis test. The result of this study is that Training has a significant effect on employee performance with the linear regression equation Y = 25,740 + 0,231 X1, the correlation value of 0.236 means that the two variables have a low level of relationship. The determination value is 05,6% The hypothesis test is obtained from the calculated t value > t table or (2,368 > 0,200). Thus, H0 was rejected by H1, which means that there is a significant influence between training on the performance of PT employees. Cipta Mandiri Agung Jaya Soekarno Hatta Airport. Work stress has a significant effect on employee performance with the linear regression equation Y = 20,911 + 0,356 X2, the correlation value of 0.390 means that the two variables have a low level of relationship. The determination value is 15.2%. The hypothesis test obtained calculates the t value > t table or (4,124 > 0,200). Thus, H0 was rejected by H1, which means that there is a significant influence between work stress on the performance of PT employees. Cipta Mandiri Agung Jaya Soekarno Hatta Airport. Training and work stress have a significant effect on employee performance with linear regression equation Y = 21,017 + 0.006X1 + 0,359X2. A correlation value of 0.390 means it has a low level of relationship. The determination coefficient value is 15.2% while the rest is 84.8% which is influenced by other factors. The hypothesis test obtained the value of F calculated > F table or (8,415 > 3,09). Thus, H0 was rejected by H3 to be accepted, which means that there is a significant influence on the simultaneous training and work stress on the performance of PT employees. Cipta Mandiri Agung Jaya Soekarno Hatta Airport